(untitled) (Journal of Economic Research & Business Administration, 2016)
The paper discusses the key prerequisites for the development of Kazakhstan’s model of civil service and the organization of work of civil servants. The main ideas are devoted to the analysis of the necessity of studying foreign experience of the advanced countries in the sphere of civil service in terms of creating its own model of a modern, professional and autonomous state apparatus in the Republic of Kazakhstan. It highlights the issue of the study samples of international experience, which will boost the creation of a modern and effective human resources management system, taking into account the specifics of the Kazakhstan development and statehood. The experience of leading countries in attracting professional staff in the civil service system and promote their career such as Singapore, Canada and Korea. The provisions of the research can be applied both in theoretical research and in the organization of the activities of state bodies and civil servants.